GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 12858 species occurrences available in GBIF matching the query: TaxonKey: Rhodiola rosea L.. The dataset includes 12858 records from 167 constituent datasets: 51 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 66 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 269 records from Phanerogamic Botanical Collections (S). 193 records from Jordal. 7 records from University of Vienna, Institute for Botany - Herbarium WU. 225 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 2 records from Online Atlas of vascular plants 2012-2020. 228 records from Naturalis Biodiversity Center (NL) - Botany. 2 records from SANT herbarium vascular plants collection. 1 records from Collection du Musée d'Histoire Naturelle de Nice. 2 records from Harriet Irving Botanical Gardens (HIBG). 30 records from Species plots from the Norwegian Vegetation Mapping Programme. 14 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 1 records from Some Plant Specimens from KUN, IBSC, NAS Herbarium in China from 1900 to 1950. 2 records from Plant Specimen from Herbarium (CDBI) in China, Chengdu Institute of Botany, Chinese Academy of Sciences. 12 records from Phytochorologie des départements français. 164 records from BioFokus. 66 records from Herbier Louis-Marie (QFA) - Collection de plantes vasculaires. 79 records from Vascular plant herbarium, Agder naturmuseum og botaniske hage. 1 records from CESJ - Herbário Leopoldo Krieger. 513 records from Artdata. 1 records from MBM - Herbário do Museu Botânico Municipal. 1 records from Stabbetorp - Floristiske registreringer 2016. 52 records from OHN. 1 records from Données ONF Faune-Flore-Fonge. 3 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Skye Estate during October 1995 â October 2004.. 10 records from Norwegian Biodiversity Information Centre - Other datasets. 2 records from Australia's Virtual Herbarium. 27 records from Fundación Biodiversidad, Real Jardín Botánico (CSIC): Anthos. Sistema de Información de las plantas de España. 28 records from Herbier de Strasbourg. 191 records from Vascular Plant Herbarium, UiB. 2 records from Kathryn Kalmbach Herbarium. 8 records from Consortium of California Herbaria. 26 records from iNaturalist Research-grade Observations. 3 records from UCBG TAPIR Provider. 20 records from CONN. 4 records from H.A. Stephens Herbarium. 16 records from University of Lethbridge Herbarium (LEA). 10 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Vascular Plants. 8 records from NINA botanical collection. 20 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 1 records from A common plants survey of vascular plants in South Northumberland and Durham, United Kingdom. 1 records from Herbarium specimens of Association des Naturalistes de la vallée du Loing (ANVL). 6 records from Herbarium specimens of Société des Sciences Naturelles et Mathématiques de Cherbourg (CHE). 2 records from Occurrence Data of Vascular Plants collected or compiled for the Flora of Bavaria. 2 records from OAC-BIO Herbarium. 35 records from naturgucker. 1 records from Scottish Natural Heritage - Standing Waters Database. 1 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the LÃ¬ and Coire Dhorrcail Estate during June 2001.. 743 records from INPN - Données flore des CBN agrégées par la FCBN. 1 records from CeDoc de Biodiversitat Vegetal: BCN-Seeds. 6 records from Vascular plant specimens of Akita Prefectural Museum. 14 records from Jardin botanique de Montréal (JBM). 5 records from FKSE-Herbarium specimens of Faculty of Symbiotic Systems Science, Fukushima University, Japan. 9 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 2 records from Angiospermatatophytina Collection of Saitama Museum of Natural History. 3 records from Plant (NSMK-PL). 4 records from Mongolian Plant (MMNH-PL). 19 records from svalbardflora.no. 28 records from Tiroler Landesmuseum Ferdinandeum. 7 records from Tropicos Specimen Data. 3 records from Natural History Museum (London) Collection Specimens. 13 records from Natural History Museum, Vienna - Herbarium W. 43 records from NatureServe Network Species Occurrence Data. 1 records from Ireland's BioBlitz. 3 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 5 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 57 records from Dataflos. 4 records from Ibaraki Nature Museum, Vascular Plants collection. 3 records from Leiner-Herbar Konstanz. 8 records from NMNH Extant Specimen and Observation Records. 1 records from Universität Salzburg. 1 records from Korean Ethnobotany Database. 3 records from Canadian Museum of Nature Herbarium. 47 records from Vascular Plant Collection - University of Washington Herbarium (WTU). 65 records from Herbarium (ICEL). 51 records from Herbarium (AMNH). 1022 records from Observational database of Icelandic plants. 5 records from Colección de plantas vasculares del herbario de la Universitat de València (VAL).. 3 records from Herbario de Plantas Vasculares de la Universidad de Salamanca: SALA. 25 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 1 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO. 3 records from Aranzadi Zientzi Elkartea. 2 records from CIBIO, Alicante:ABH-GBIF. 2 records from Herbario de la Universidad de Sevilla. 2 records from Herbario de la Universidad de Sevilla, SEV-Historico. 2 records from Botanic Garden of the Finnish Museum of Natural History. 7 records from Herbarium of Jyväskylä University Museum. 2 records from Plant in Baekdu Mountain (KIDR-PL). 1 records from herbario. 170 records from Herbarium Faeroense. 1 records from Botanical Museum, Copenhagen. Database of type specimens. 9 records from Herbarium Berolinense. 1 records from Staatliches Museum für Naturkunde Stuttgart, Herbarium. 1 records from Biologiezentrum Linz. 1 records from United States National Plant Germplasm System Collection. 108 records from Nordic Genetic Resources. 163 records from Floristische Kartierung Österreichs - Mapping the Flora of Austria. 2 records from USU-UTC Specimen Database. 1 records from Universidad Politécnica de Madrid, Dpto. Biología Vegetal, Banco de Germoplasma. 1 records from Institut Botanic de Barcelona, BC-Histórico. 4 records from Angiosperm specimens of Iwate Prefectural Museum. 37 records from Harvard University Herbaria. 4 records from inatura - Erlebnis Naturschau Dornbirn. 11 records from EURISCO, The European Genetic Resources Search Catalogue. 1 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 7 records from Plant specimens depodited in Osaka Museum of Natural History, Japan.. 49 records from Vascular Plants, Observations, Oslo (O). 4 records from FloVegSI - Floristical and fitocenological database of ZRC SAZU. 2 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 1 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 2 records from MPM Milwaukee Public Museum Herbarium. 1 records from R. L. McGregor Herbarium Vascular Plants Collection. 3 records from EDIT - ATBI in Mercantour/Alpi Marittime (France/Italy). 15 records from Vascular Plant Specimen Database of Kanagawa Prefectural Museum of Natural History. 1 records from Gunma Museum of Natural History, Vascular Plant Specimen. 61 records from Plant. 5 records from Biological and palaeontological collection and observation data MNHNL. 36 records from Sukkulentensammlung Zürich. 5 records from Herbarium Senckenbergianum (FR). 1 records from Collection Aves (bird skeletons) SMF. 1 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO-Briof. 2 records from Plant of Folklore (KIDR-PL). 1 records from E39 Lyngdal - Ålgård. 2 records from Herbarium specimens of the Muséum d'Histoire Naturelle of Aix-en-Provence (AIX). 4 records from VIT Herbarium - Vascular Plants (The Natural History Museum of Alava). 44 records from FloraCAT: Banco de datos de los cormófitos de Cataluña. 2 records from Herbarium specimens, Harmas J.H. Fabre (FABR - Sérignan-du-Comtat) of the Muséum national d'Histoire naturelle (MNHN - Paris). 3 records from Faun. 11 records from Flora d'Andorra. 215 records from Lund Botanical Museum (LD). 2 records from Geographically tagged INSDC sequences. 2373 records from Norwegian Species Observation Service. 8 records from Vascular Plants, Museum of Archaeology, University of Stavanger. 320 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 7 records from SBT-Living. 8 records from Carnet en Ligne. 1 records from Seed collection – Dead seeds for evaluation and observation purposes. 88 records from Royal Botanic Garden Edinburgh Herbarium (E). 1 records from All observations extracted from the Flora of Northumberland and Durham 1831. 22 records from Botany (UPS). 1 records from Herbier du Québec (QUE) – Collection de plantes vasculaires. 2 records from University of British Columbia Botanical Garden Collections (UBCBG). 5 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 5 records from Verneplan Hjerkinn karplanter. 136 records from Vascular plant herbarium, Tromsø Museum. 1 records from BHCB - Herbário da Universidade Federal de Minas Gerais. 271 records from Vascular plant herbarium, NTNU University Museum. 1 records from Données ONF Faune-Flore-FOnge. 2533 records from Vascular Plants, Field notes, Oslo (O). 10 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 2 records from Universidad de Navarra, Herbarium: PAMP-Vascular Plants. 19 records from Ecofact. 1 records from Green Plant Herbarium (TRT). 1 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on Quinag in 2006-2007. 28 records from Gothenburg Herbarium - General (GBIF:IH:GB:Herbarium). 46 records from SysTax - Botanical Gardens. 506 records from Vascular Plant Herbarium, Oslo (O). 12 records from Flora von Deutschland (Phanerogamen). 33 records from E. C. Smith Herbarium (ACAD). 2 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Sandwood Estate during 1998 â 2006.. 91 records from National Trust for Scotland - NTS Properties Species Records 1800-2013. 661 records from Vascular plant field notes, NTNU University Museum. 1 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Nevis Estate during summer 2003.. 6 records from BoGART. 24 records from Some Plant Specimens from PE Herbarium in China from 1900 to 1950. 1 records from Herbarium specimens of Limoges university (LIMO). Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences